2018
DOI: 10.5194/esd-9-459-2018
|View full text |Cite
|
Sign up to set email alerts
|

European climate change at global mean temperature increases of 1.5 and 2 °C above pre-industrial conditions as simulated by the EURO-CORDEX regional climate models

Abstract: Abstract. We investigate European regional climate change for time periods when the global mean temperature has increased by 1.5 and 2 • C compared to pre-industrial conditions. Results are based on regional downscaling of transient climate change simulations for the 21st century with global climate models (GCMs) from the fifth-phase Coupled Model Intercomparison Project (CMIP5). We use an ensemble of EURO-CORDEX highresolution regional climate model (RCM) simulations undertaken at a computational grid of 12.5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(107 citation statements)
references
References 46 publications
18
89
0
Order By: Relevance
“…In the “ South ,” the mean changes are −0.05 ms −1 (−1.7%) with a range from −0.21 to +0.07 ms −1 (−6 to +5%). The numbers are in broad agreement with the results of Kjellström et al (), when inspecting their maps of Europe over Switzerland. The largest decreases are found for SMHI‐RCA4 simulations.…”
Section: Resultssupporting
confidence: 91%
“…In the “ South ,” the mean changes are −0.05 ms −1 (−1.7%) with a range from −0.21 to +0.07 ms −1 (−6 to +5%). The numbers are in broad agreement with the results of Kjellström et al (), when inspecting their maps of Europe over Switzerland. The largest decreases are found for SMHI‐RCA4 simulations.…”
Section: Resultssupporting
confidence: 91%
“…For instance, our models of leaf flushing predict reduced geographical variability in phenology in the future (from day 94 to 160 -Figure 1d- and from day 94 to 147 – Figure 3d-), as has been reported worldwide (Ma, Huang, Hänninen, & Berninger, 2018). This is mostly explained by larger advances in the phenology of populations at colder sites than those at warmer sites, likely as a consequence of the larger increases in winter temperatures that happen in the North (Kjellström et al, 2018). Survival of young trees is predicted to decrease at the margins of the distribution, but less markedly than is predicted by species distribution models (Kramer et al, 2010; Stojnic et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in near-surface wind speed are associated with a large spread among individual ensemble members at both warming levels. Kjellström et al (2018) examined European climate change for global mean temperature increases of 1.5 and 2 ∘ C above preindustrial conditions. They found that relatively large areas over the North Atlantic and some parts of the continent show decreasing wind speed, while some ocean areas in the far north show increasing wind speed.…”
Section: Atmospheric Model Forcingmentioning
confidence: 99%